The Transition To Artificial Intelligence -Based Solutions For Improving Energy Efficiency In Urban Environments - Ikram MENAI; Hana SALAH SALAH; Sara KHELIL; Amina AIDAOUI; Fatima Zahra DJOUAD (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The urban landscape is rapidly evolving towards sustainable, energy-efficient practices, thanks in large part to the integration of artificial intelligence (AI) solutions. This study explores the dynamic transition to AI-based technologies for improving energy efficiency in urban environments. AI is emerging as a powerful tool for optimizing energy consumption, streamlining infrastructure operations and fostering smart, resilient urban ecosystems. The study examines various applications of AI, highlighting the essential role advanced technologies play in revolutionizing conventional approaches to urban energy management, and illustrating how these technologies can contribute to the creation of self-sufficient urban spaces. It examines the implementation of AIbased energy networks, smart energy storage solutions and the integration of renewable energy into urban planning, and also looks at the potential challenges and ethical considerations associated with its adoption. It addresses issues such as data privacy, algorithmic biases and the need for transparent decision-making processes. This research is a literature review that aims to contribute to the current discourse on creating smart, energyefficient cities.